The Role of Medical Laboratory Specialists and Phlebotomists in Reducing Errors and Enhancing Patient Safety - Hanadi Faleh Salem Albalawi, Jasser Hamed Hamad Almutiri, Majed Abdullah Alqahtani, Jawaher Abdulaziz Alsubaie, Mashaal Saad A Abo Glead, Aminah Ahmad Mansoor Tamah, Sawsan Saeed Mohammed Al Jayzani, Ahmed Mufarah Alanazi (Journal of International Crisis and Risk Communication Research, 2024)
Medical and clinical laboratories play a critical role in healthcare by providing accurate diagnostic data that informs clinical decisions and treatment plans. However, errors in the pre- and post-analytical stages of laboratory testing can compromise patient safety and clinical outcomes. This review explores the nature and impact of pre- and post-analytical errors, highlighting common issues such as sample collection errors, inaccurate labeling, poor handling of transport, and delays in reporting results. The critical role of medical laboratory professionals, technicians, and phlebotomists in reducing these errors through adherence to protocols and quality assurance practices is emphasized. Furthermore, the research examines the transformative impact of technological advances, including automation, laboratory information management systems (LIMS), artificial intelligence, and point-of-care testing (POCT), in reducing errors and improving the reliability of laboratory results. Addressing the challenges facing laboratory services and leveraging opportunities for innovation is essential to improving diagnostic accuracy, enhancing patient safety, and achieving better healthcare outcomes.